Sustainability Metrics in Emerging Markets: Analyzing ESG Scores Through Financial Returns and Risks - Lirisanti, Dika; Husodo, Zaäfri Ananto (Indonesian Journal of Advanced Research, 2025)
This study examines the impact of stock returns and risks on ESG (Environmental, Social, and Governance) scores in emerging Asian markets during the COVID-19 pandemic. Utilizing panel data from Refinitiv Eikon for March 2019 to March 2022, this research investigates how returns, risks, and control variables such as Excess Market Return, SMB, HML, and Liquidity influence ESG scores. The findings reveal that returns and risks exhibit differential impacts on ESG scores, with social factors emerging as the most influential ESG component. These results highlight the nuanced role of financial performance in driving ESG metrics during crises, particularly in less-developed markets.